2009
DOI: 10.1051/radiopro/20095021
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radionuclide and heavy metal contamination of the Yenisei River on cytogenetics of aquatic plantElodea canadensis

Abstract: The study was done to determine concentrations of radionuclides and heavy metals and to evaluate the frequency of chromosomal aberrations in samples of Elodea canadensis, a submerged plant, collected in different parts of the Yenisei River. Samples were collected in the area subjected to radioactive impact of the Mining-and-Chemical Combine (MCC) at Zheleznogorsk and in the control areas, upstream of the MCC. The investigations showed that Elodea biomass in the area affected by MCC operation contained a long i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…Водные виды растений сравнительно недавно стали при-меняться в качестве биоиндикаторов техногенного загрязнения, и цитоге-нетические работы с их использованием немногочисленны [13,16]. К числу массовых видов макрофитов, вегетирующих в районе реки Енисей, как в зоне техногенного загрязнения, так и на фоновых участках, относится Elodea canadensis Michx.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Водные виды растений сравнительно недавно стали при-меняться в качестве биоиндикаторов техногенного загрязнения, и цитоге-нетические работы с их использованием немногочисленны [13,16]. К числу массовых видов макрофитов, вегетирующих в районе реки Енисей, как в зоне техногенного загрязнения, так и на фоновых участках, относится Elodea canadensis Michx.…”
Section: Introductionunclassified
“…В результате ряда исследований в 2003-2006 гг. [10,16] и в 2011-2012 гг. [26] были подробно изучены ци-тогенетические характеристики элодеи канадской.…”
Section: Introductionunclassified
“…While, however, mechanisms of accumulation and distribution of stable isotopes of heavy metals in aquatic plants have been thoroughly discussed in the literature, there are very few studies addressing the corresponding aspects of behavior of radionuclides. Laboratory experiments showed that artificial radionuclides are not uniformly distributed among different components of plant biomass. Localization of radionuclides in the biomass of macrophytes determines further migration of radionuclides in the aquatic ecosystem, doses to specific cellular constituents and the subsequent radiotoxic effect …”
Section: Introductionmentioning
confidence: 99%
“…4À9 Localization of radionuclides in the biomass of macrophytes determines further migration of radionuclides in the aquatic ecosystem, doses to specific cellular constituents and the subsequent radiotoxic effect. 10 In most previous studies, aquatic plants were subjected to sequential extraction procedures to reveal mechanisms of accumulation of heavy metals. 11,12 There is, however, no generally accepted sequential extraction scheme for aquatic plants, similar to the Tessier procedure for soils and sediments.…”
Section: ' Introductionmentioning
confidence: 99%
“…The sources of 241 Am in aquatic ecosystems are discharges from nuclear fuel reprocessing plants and decay of 241 Pu. 241 Am is detected in sediments and aquatic weeds of the Yenisei River [1,2] subjected to radioactive contamination from the Mining-and-Chemical Combine (ROSATOM) (Zheleznogorsk, 60 km downstream of the city of Krasnoyarsk). 241 Am, along with plutonium, dominates long term radiotoxicity.…”
Section: Introductionmentioning
confidence: 99%